BCD design and implementation of a stochastic brane machine - David, Maria Pamela C. (2008)
Brane calculi are a family of process calculi where actions are tightly coupled to membranes. In addition to the formalisms in stochastic π-calculus that allow the creation of models of concurrently executing and communicating processes, brane calculus provides a framework for spatial organization. Correlating the spatio-temporal location of an object with its capabilities for interaction is a very important aspect in modeling biological phenomena, from simple biochemical reactions to more complex events such as viral pathogenesis. The restrictions provided by the reduction rules of brane calculus should provide a more natural environment for modeling events where the occurrence or non-occurrence of an interaction is influenced by the location and compatibility of reactants, as well as non-deterministic factors. Currently, however, no tool exists for implementing brane calculus models. Here, the design and implementation of a tool for implementing brane calculus models. Here, the design and implementation of a tool for implementing such models is described.